Architecture

# Which Is A Factor Of 18X2 + 3X − 6? How Do You Factor 18X^2+3X

Quadratic polynomial can be factored using the transformation ax^{2}+bx+c=aleft(x-x_{1}
ight)left(x-x_{2}
ight), where x_{1} and x_{2} are the solutions of the quadratic equation ax^{2}+bx+c=0.

You are watching: Which is a factor of 18×2 + 3x − 6?

All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: frac{-b±sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
Factor the original expression using ax^{2}+bx+c=aleft(x-x_{1}
ight)left(x-x_{2}
ight). Substitute frac{-1+sqrt{31}}{6} for x_{1} and frac{-1-sqrt{31}}{6} for x_{2}.

2(x-1)2-50=0 Two solutions were found : x = 6 x = -4 Step by step solution : Step 1 :Equation at the end of step 1 : 2 • (x – 1)2 – 50 = 0 Step 2 : 2.1 Evaluate : (x-1)2 = x2-2x+1 …
displaystyle{18}{x}^{{2}}+{3}{x}-{10}={left({3}{x}-{2}
ight)}{left({6}{x}+{5}
ight)} Explanation:You need to find how to split the middle term first.Use an AC Method:Look for a pair of …
18×2+9x-14 Final result : (3x – 2) • (6x + 7) Step by step solution : Step 1 :Equation at the end of step 1 : ((2•32×2) + 9x) – 14 Step 2 :Trying to factor by splitting the middle term …

5×2+6x+30=0 Two solutions were found : x =(-6-√-564)/10=(-3-i√ 141 )/5= -0.6000-2.3749i x =(-6+√-564)/10=(-3+i√ 141 )/5= -0.6000+2.3749i Step by step solution : Step 1 :Equation at the end of …
5×2+8x-36=0 Two solutions were found : x = -18/5 = -3.600 x = 2 Step by step solution : Step 1 :Equation at the end of step 1 : (5×2 + 8x) – 36 = 0 Step 2 :Trying to factor by splitting …
8×2+6x-9=0 Two solutions were found : x = -3/2 = -1.500 x = 3/4 = 0.750 Step by step solution : Step 1 :Equation at the end of step 1 : (23×2 + 6x) – 9 = 0 Step 2 :Trying to factor by …
More Items

Quadratic polynomial can be factored using the transformation ax^{2}+bx+c=aleft(x-x_{1}
ight)left(x-x_{2}
ight), where x_{1} and x_{2} are the solutions of the quadratic equation ax^{2}+bx+c=0.
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: frac{-b±sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.

Factor the original expression using ax^{2}+bx+c=aleft(x-x_{1}
ight)left(x-x_{2}
ight). Substitute frac{-1+sqrt{31}}{6} for x_{1} and frac{-1-sqrt{31}}{6} for x_{2}.
Quadratic equations such as this one can be solved by a new direct factoring method that does not require guess work. To use the direct factoring method, the equation must be in the form x^2+Bx+C=0.This is achieved by dividing both sides of the equation by 18
Let r and s be the factors for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where sum of factors (r+s)=−B and the product of factors rs = C
Two numbers r and s sum up to -frac{1}{3} exactly when the average of the two numbers is frac{1}{2}*-frac{1}{3} = -frac{1}{6}. You can also see that the midpoint of r and s corresponds to the axis of symmetry of the parabola represented by the quadratic equation y=x^2+Bx+C. The values of r and s are equidistant from the center by an unknown quantity u. Express r and s with respect to variable u.

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు